Enhanced Nile tilapia meat quality by the metabolomic effects of Tenebrio molitor larval meal dietary supplement - Qin Liu; Jian Li; Jiale Liu; Yishui Cai; Yang Luo; Tajie Sangzhu; Bo Ye; Manjun Yang (Applied Food Research)
The rising cost of soybean meal has posed challenges for tilapia (Oreochromis niloticus) farming. This study aimed to explore the use of Tenebrio molitor larval meal (TLM) as a sustainable alternative, leveraging its ability to convert agro-food wastes into high-quality feed. Replacing 15 %, 30 %, and 60 % of soybean meal with TLM in tilapia diets significantly improved the meat quality. Furhermore, aquatic extracts of tilapia dorsal muscle exhibited enhanced antioxidant activity, as indicated by increased scavenging rates of 2, 20-azinobis(3-ethylben-zothiazoline 6-sulfonate) (ABTS), 2, 2- diphenyl-1-picrylhydrazyl (DPPH), and hydroxyl radical, along with elevated ferric reducing antioxidant potential (FRAP) values. Metabolomic analysis revealed increased abundance of amino acids and fatty acids in the liver, with glutathione metabolism identified as a key contributing pathway. Key metabolic pathways, including fatty acid synthesis via fatty acid synthase (FAS), carboxylase (ACC), and acetyl Co-A, as well as protein biosynthesis via glutamine synthetase (GS) and glutamate synthase (GOGAT), were activated. Additionally, enhancement of the tricarboxylic acid (TCA) cycle further supported biosynthetic activity. Our findings elucidate the metabolomic mechanisms through which TLM improves tilapia meat quality, offering a viable strategy for sustainable aquaculture feed formulations.